1990
DOI: 10.1016/0014-5793(90)80768-e
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor stimulates protein kinase C translocation in PC12 cells

Abstract: The effect of nerve growth factor (NGF) on the activity and intracellular localization of protein kinase C (PKC) in pheochromocytoma PC12 cells was studied. By using immunoblotting, immunofluorescence method and phorbol ester binding, NGF was found to induce PKC translocation from the cytoplasm into the cell membrane. This process was accompanied by an increase in the protein kinase activity in the membrane fraction. Translocation was completely blocked by H-7, a protein kinase inhibitor potentiating the neuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…These results suggest that phosphorylation of SNAP-25 by some types of PKC may be involved in NGF-induced neurite outgrowth. It is interesting that NGF-induced protein translocation from cytoplasm to plasma membrane is also reported in PKC itself (Kondratyev et al, 1990) and in GAP-43 (Van Hooff et al, 1989). It will be interesting to study relationships between protein translocation and neurite extension to gain an insight into the molecular mechanisms of neuronal differentiation.…”
Section: Figmentioning
confidence: 94%
“…These results suggest that phosphorylation of SNAP-25 by some types of PKC may be involved in NGF-induced neurite outgrowth. It is interesting that NGF-induced protein translocation from cytoplasm to plasma membrane is also reported in PKC itself (Kondratyev et al, 1990) and in GAP-43 (Van Hooff et al, 1989). It will be interesting to study relationships between protein translocation and neurite extension to gain an insight into the molecular mechanisms of neuronal differentiation.…”
Section: Figmentioning
confidence: 94%
“…Additional previous studies of short-term (less than 1 h) NGF-treated PC12 cells have demonstrated the translocation to the particulate subcellular fraction of PKCa (Kondratyev et al, 1990) and PKCQ (Wooten et al, 1994), and a selective activation of PKCE kinase activity (Ohmichi et al, 1993). These rapid effects may be related to the early signal transduction events initiated by NGF binding to the Trk proto-oncogene receptor expressed in PC12 cells (Kaplan et al, 1991); however, because NGF-induced neuritogenesis by PC12 cells occurs over a prolonged course (1-7 days) (Greene and Tischler, 1976), in the present study we examined the expression of several PKC isoforms at later time points.…”
Section: Ngf Differentially Regulates Individual Pkc Isoforms In Pc12mentioning
confidence: 95%
“…PKC activators, such as phorbol esters, mimic certain biological activities of NGF in PC12 cells (9,10). In addition, NGF has been shown to stimulate translocation of PKC activity and activation of specific isoforms (11,12). Likewise, certain NGF-specific transcripts are induced in response to PKC (13).…”
mentioning
confidence: 99%